Linear Control of Fractional-Order Financial Chaotic Systems with Input Saturation - Junhai Luo; Guanjun Li; Heng Liu (Discrete Dynamics in Nature and Society)
In this paper, control of fractional-order financial chaotic systems with saturated control input is investigated by means of state-feedback control method. The saturation problem is tackled by using Gronwall-Bellman lemma and a memoryless nonlinearity function. Based on Gronwall inequality and Laplace transform technique, two sufficient conditions are achieved for the asymptotical stability of the fractional-order financial chaotic systems with fractional orders 0 < α ≤ 1 and 1 < α < 2, respectively. Finally, simulation studies are carried out to show the effectiveness of the proposed linear control method.